Genetic variability and trait relationship in cherry tomato (Solanum lycopersicum L. var. cerasiforme (Dunnal) A. Gray) (Bangladesh Journal of Botany, 2013)
Nine traits of 11 cherry tomato (Solanum lycopersicum L.) var. cerasiforme (Dunal) A. Gray) inbred lines exhibited a wide range of genetic variability. High geno- and phenotypic coefficients of variation were obtained for individual fruit weight (68.16 and 74.23%, respectively) followed by number of fruits/plant (58.8 and 68.34%, respectively). High estimates of heritability, genetic advance and genotypic coefficient of variation for the traits of individual fruit weight, number of fruits and clusters/plant were controlled by additive gene action indicating the possibility of selection to improve these characters. Fruit yield/plant showed low heritability along with low genetic advance and did not show significant and positive correlation with the remaining characters. It indicates that improvement of high yield through selection is difficult, rather hybridization can be effective for improving the fruit yield/plant. Among the lines, CH154 produced the highest number of fruits/plant (291) and highest fruit yield (1.89 kg/plant and 63.4 t/ha) and can be selected for cultivation under Bangladesh condition. DOI: http://dx.doi.org/10.3329/bjb.v41i2.13443 Bangladesh J. Bot. 41(2): 163-167, 2012 (December)